Healthcare Under Fire: Conflict, Human Security, and Post-War Recovery in Ukraine - Kuckreja,Sargam (2025)
This thesis investigates the weaponisation of healthcare in Ukraine during the ongoing conflict, analysing how deliberate attacks on medical infrastructure are not just violations of humanitarian law but systemic assaults on development, governance, and human security. Framed through a three-stage model: Disruption, Destabilisation, and Reconstruction, the study draws on Amartya Sen’s Development as Freedom, the Human Security Framework, and Post-Conflict Reconstruction Theory to situate healthcare destruction as both a tactical act and a structural crisis. Methodologically, the research employs a hybrid approach that combines Natural Language Processing (NLP) tools, Latent Dirichlet Allocation (LDA), BERTopic, sentiment analysis, and Named Entity Recognition (NER), with manual thematic analysis of 298 humanitarian documents published between 2022 and 2025. These texts were systematically analysed to identify shifts in emotional tone, thematic focus, and institutional discourse across each stage of the conflict. Findings show that healthcare has become a political instrument in modern warfare, with Ukraine's case illustrating how its destruction depletes institutional trust, exacerbates civilian vulnerability, and obstructs long-term recovery. Despite global humanitarian efforts, effective reconstruction remains conditional, constrained by insecurity, weak governance, and contested narratives. The thesis concludes that targeting health systems creates development vacuums which, when rebuilt, become critical sites for post-war legitimacy, resilience, and reform.
Keywords: healthcare weaponisation; Ukraine conflict; development; human security; post-conflict recovery